Exhaled Breath Condensate Analysis after Long Distance Races - Araneda, O. F.; Guevara, A. J.; Contreras, C.; Lagos, N.; Berral, F. J. (International Journal of Sports Medicine, 2012)
The impact of an endurance race on pulmonary pro-oxidative formation and lipoperoxidation was evaluated using exhaled breath condensate (EBC). 3 groups of 12, 12 and 17 healthy recreational runners of both sexes ran 10, 21.1 and 42.2 km, respectively. EBC samples were obtained before the run and at 20 and 80 min post run. Concentrations of H2O2, NO2 − , malondialdehyde and pH were determined. The 10 km group showed no post-run variations for H2O2 and NO2 −  concentrations. The 21.1 km group showed significant increments for NO2 − , and H2O2 concentrations in 20 min and 80 min samples. The 42.2 km group, showed increased NO2 −  concentration in 20 min and 80 min samples, while H2O2 concentration increased only in the 20 min sample. In the 10 and 42.2 km groups neither malondialdehyde concentration nor pH showed differences. The 42.2 km group exhibited ΔH2O2 and ΔNO2 −  medians higher than the 10 km group. ΔpH median decreased in 21.1 and 42.2 km groups, exhibiting values significantly lower than the 10 km group. ΔH2O2 y ΔNO2 −  correlated directly with race time, while ΔpH, correlated inversely. In conclusion, intense prolonged exercise favors the increase in pulmonary pro-oxidative levels, with no modifications on lipoperoxidation. Running time relates to the magnitude of acute post exercise pro-oxidative formation.
Keywords: breath analysis; lung oxidative stress; physical exercise; long distance runners